y = 2x² - 5x - 18
2x - 5x - 18 = 0
x = -(-5) +/- √((-5)² - 4(2)(-18))
2(2)
x = 5 +/- √(25 + 144)
4
x = 5 +/- √(169)
4
x = 5 +/- 13
4
x = 5 + 13 x = 5 - 13
4 4
x = 18 x = -8
4 4
x = 4 1/2 x = -2
-----------------------------------------------------------------------------------------------
y = 2x² - 5x - 18
y = 2(4 1/2)² - 5(4 1/2) - 18
y = 2(20 1/4) - 22 1/2 - 18
y = 40 1/2 - 22 1/2 - 18
y = 18 - 18
y = 0
(x, y) = (4 1/2, 0)
or
y = 2x² - 5x - 18
y = 2(2)² - 5(2) - 18
y = 2(4) - 10 - 18
y = 8 - 10 - 8
y = -2 - 8
y = -10
(x, y) = (2, -10)